2022
DOI: 10.1186/s13046-022-02338-w
|View full text |Cite
|
Sign up to set email alerts
|

Oncometabolites drive tumorigenesis by enhancing protein acylation: from chromosomal remodelling to nonhistone modification

Abstract: Metabolites are intermediate products of cellular metabolism catalysed by various enzymes. Metabolic remodelling, as a biochemical fingerprint of cancer cells, causes abnormal metabolite accumulation. These metabolites mainly generate energy or serve as signal transduction mediators via noncovalent interactions. After the development of highly sensitive mass spectrometry technology, various metabolites were shown to covalently modify proteins via forms of lysine acylation, including lysine acetylation, crotony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 210 publications
(249 reference statements)
0
26
0
Order By: Relevance
“…The great variability among lipids, in terms of their structure and properties, contributes to the remarkable diversity of lipid modifications. Among them, the most important is the acylation modification of proteins, in which FA is covalently linked to the peptide chain in the form of an acyl group 57 . In addition to classical lysine acetylation, many novel acylation modifications of histone and non-histone proteins, such as malonylation (Kma, mediated by malonyl-CoA), β-hydroxybutyrylation (Kbhb, mediated by β-hydroxybutyric acid; BHB), isoprene (mediated by intermediates of cholesterol synthesis), and long-chain fatty acid (LCFA) acylation, have been identified 58 .…”
Section: Specific Functions Of Lipids In Tumor Cellsmentioning
confidence: 99%
“…The great variability among lipids, in terms of their structure and properties, contributes to the remarkable diversity of lipid modifications. Among them, the most important is the acylation modification of proteins, in which FA is covalently linked to the peptide chain in the form of an acyl group 57 . In addition to classical lysine acetylation, many novel acylation modifications of histone and non-histone proteins, such as malonylation (Kma, mediated by malonyl-CoA), β-hydroxybutyrylation (Kbhb, mediated by β-hydroxybutyric acid; BHB), isoprene (mediated by intermediates of cholesterol synthesis), and long-chain fatty acid (LCFA) acylation, have been identified 58 .…”
Section: Specific Functions Of Lipids In Tumor Cellsmentioning
confidence: 99%
“…PTM crosstalk is important for regulation of biological processes [6062]. Here, we found that multiple PTMs occur on the same lysine of the same protein, for example 392 lysine sites were commonly modified by lactylation (Kla), crotonylation (Kcr), and 2-hydroxyisobutyrylation (Khib) (Figure S20, Table S26 and S27).…”
Section: Discussionmentioning
confidence: 93%
“…Free fatty acids not only fuel cancer progression through β-oxidation, but also serve as one of major metabolic resources generate abundant intermediate product within cells, such as lactate, Succ-CoA, Ac-CoA and BHB, which provide acyl-groups to covalently modify proteins, and then regulate their activity, subcellular localization or activated expression. These play dramatic roles in metabolomic-epigenetic and metabolomic-proteomic signaling in tumors(Fu et al, 2022; Sabari et al, 2017). On the other hand, it has been reported that low and high concentrations of FFA uptake by cancer cells could have either proliferative or lipotoxic effects, respectively, for example, arachidonic acid promotes proliferation at low concentrations but at high concentrations induces lipotoxicity through ferroptosis.…”
Section: Discussionmentioning
confidence: 99%